High-Throughput Isolation of Nucleic Acids from Soil - Claudia Chiodi; Matteo Moro; Andrea Squartini; Giuseppe Concheri; Francesco Occhi; Flavio Fornasier; Massimo Cagnin; Giovanni Bertoldo; Chiara Broccanello; Piergiorgio Stevanato (Soil Systems, 2019)
DNA-based technologies have become widespread tools for soil microbiological analyses in recent years. DNA extraction from the soil is a key step for these approaches: it is a challenge for researchers as it is still both expensive and time-consuming when large surveys are planned. The aim of this study was to develop a high-throughput automated protocol for DNA extraction and purification from soil. The protocol was based on the BioSprint 96 platform and compared for validation with another automated procedure and two commercial column-based kits. To evaluate the performances of the protocols, we considered quality, quantity, and amplifiability of the isolated DNA. The material isolated by means of the four protocols showed appropriate yield and quality and positive amplification. The isolation protocol presented here provided similar results to those of the commercial kits but with two essential differences: cost and time for DNA extraction were drastically reduced. This rapid and efficient protocol is envisaged as ideal to standardize soil studies and treat large numbers of samples, representing a workable alternative to low-throughput and expensive manual extraction methods.